PENGGUNAAN METODE BAR BENDING SCHEDULE UNTUK MENGANALISIS KEBUTUHAN & SISA (WASTE) PEMBESIAN BALOK PADA PROYEK RUMAH SAKIT ISLAM AYSHA - Dedy Dharmawansyah; Eti Kurniati; Auliya Kasyfil Aziz (Jurnal TAMBORA, 2023)
In the construction work of the Aysha Islamic Hospital structure, the reinforcement carried out experienced significant material residues. This of course can affect the cost of a job on each floor. The data obtained on the 3rd floor beam reinforcement work at the Aysha Islamic Hospital project reached 32,498.72 kg or equivalent to Rp.341,236.560.00-. The iron work experienced a lot of material residue that was still suitable for use with an estimated 0.5% iron waste which was not actually used for further work. In practice, to avoid waste in iron work, implementers need to analyze how much reinforcement is needed to build a beam. The amount of the volume of iron work must be known or obtained before the implementation of construction, because the volume of a work is the basis of planning the development budget. From the calculation results in the discussion, it is obtained that the iron requirement (kg) needed for beam work in the implementation of the Aysha Islamic Hospital Project is 163303.15 kg. The amount of waste for beam work in the implementation of the Aysha Islamic Hospital Project is 20046.98 kg. The remaining percent of the beam (%) in the implementation of the Aysha Islamic Hospital Project is Rp. 1.714.683.075.-